Young star cluster populations in the E-MOSAICS simulations - Pfeffer, Joel; Kruijssen, Diederik; Reina-Campos, Marta (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We present an analysis of young star clusters (YSCs) that form in the E-MOSAICS cosmological, hydrodynamical simulations of galaxies and their star c